Identified five variants in CFTR gene that alter RNA splicing by minigene assay - Zhang, Bingying; Zhang, Yiyin; Zhang, Yan; Liu, Xuyan; Zhang, Ran; Wang, Zhi; Pan, Fengjiao; Xu, Ning; Shao, Leping (Frontiers in Genetics, 2025)
BackgroundCystic fibrosis (CF) is a common monogenic multisystem disease caused primarily by variants in the CFTR gene. Emerging evidence suggests that some variants, which are described as missense, synonymous or nonsense variants in the literature or databases, may be deleterious by affecting the pre-mRNA splicing process.MethodsWe analyzed 27 exonic variants in the CFTR gene utilizing bioinformatics tools and identified candidate variants that could lead to splicing changes through minigene assays. Ultimately, we selected eight candidate variants to assess their effects on pre-mRNA splicing. The numbering of DNA variants is based on the complementary DNA (cDNA)sequence of CFTR (Ref Seq NM_000492.4).ResultsThis study assessed the impact of CFTR variants on exon splicing by combining predictive bioinformatics tools with minigene assays. Among the eight candidate single nucleotide alterations, five variants (c.488A>T,c.1117G>T, c.1209G>T, c.3239A>G and c.3367G>C) were identified as causing exon skipping.ConclusionOur study employed a minigene system, which offers great flexibility for assessing aberrant splicing patterns when patient mRNA samples are not accessible, to investigate the effects of exonic variants on pre-mRNA splicing. Our experimental outcomes highlight the importance of analyzing exonic variations at the mRNA level.